ТЕОРЕТИЧНІ ЗАСАДИ ВИКОРИСТАННЯ ШТУЧНОГО ІНТЕЛЕКТУ В СИСТЕМІ ПУБЛІЧНОГО УПРАВЛІННЯ ОБОРОНОЗДАТНІСТЮ ДЕРЖАВИ - Ярослав ПУСТОВІТ (Herald of Khmelnytskyi National University. Economic sciences, 2026)
The article examines the theoretical foundations for the use of artificial intelligence technologies in the system of public administration of state defense capability in the context of the transformation of the contemporary security environment and the intensive development of digital technologies. It is substantiated that artificial intelligence is gradually becoming an important factor in the modernization of the national security and defense system, creating new opportunities for improving strategic planning, information and analytical support, forecasting security threats, resource management, and decision-making support. The essence of artificial intelligence in the context of public administration science is defined, and the expediency of considering it simultaneously as a tool for strengthening the institutional and managerial capacity of the state and as a specific object of public regulation is substantiated. A multilevel approach to the use of artificial intelligence in ensuring state defense capability is proposed, encompassing strategic, institutional and managerial, operational, and technological levels. The main functions of artificial intelligence within the public administration system of state defense capability are systematized, including information and analytical, forecasting, coordination, optimization, and control functions. The key components of the public administration mechanism for the use of artificial intelligence technologies in the defense sector are identified: regulatory and legal, institutional, organizational, information and analytical, financial and economic, personnel, and monitoring and evaluation components. An author’s definition of the concept of “public administration of the use of artificial intelligence in ensuring state defense capability” is proposed. The necessity of developing an integrated model of public administration for the development, implementation, and use of artificial intelligence technologies in the defense sector is substantiated. Such a model should be based on the principles of legality, strategic expediency, responsibility, accountability, technological reliability, cyber resilience, data protection, and appropriate human oversight.